The Exposure of Long-Term Foreign Currency Bonds - Adler, Michael; Dumas, Bernard (Journal of Financial and Quantitative Analysis, 1980)
A currency is not risky because devaluation is highly likely. If the devaluation were certain, there would be no risk at all. A weak currency can be less risky than a strong currency. A strong currency does not become risky because it has been used to denominate a firm's debt.